Wicked Pleasure. - Taylor, Taryn Leigh; Mills & Boon Dare. ([Sydney NSW] : Mills & Boon Dare, 2019)
It's a wicked game they're playing...but that only makes it hotter! Breaking into enemy territory - especially a gorgeous billionaire tech playboy's home - is the sort of thing hacker AJ lives for. But a hot fling with her sexy enemy isn't part of AJ's master plan. Now AJ is playing more than just a game. As her enemy, Liam is a threat. But falling for him might just be a dangerous dare that AJ can't resist...
Keywords: Romance fiction; Contemporary romance; Fiction - Romance - Contemporary; Australian; Australian SH